2003
DOI: 10.1111/j.0742-2822.2003.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Live Three‐Dimensional Echocardiography of the Human Fetus

Abstract: The purpose of this study was to investigate the feasibility of using a new three-dimensional ultrasound system to perform fetal echocardiographic examination in real time. The device consisted of a Philips Sonos 7500 (Andover, MA) ultrasound system and a 4 MHz, 4X matrix transducer. The study was approved by the Institutional Review Board and was performed with the informed consent of the mother. The study population consisted of 12 singleton fetuses with gestational ages of 16-37 weeks. Of these, ten fetuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 11 publications
0
59
0
Order By: Relevance
“…The frame rate of the system, the number of pictures per second (the frame rate being in the region of 20-28 frames per second), is fairly adequate in order to resolve the definition of the heart as it moves. There have been some reports on real-time 3D sonographic observation of the fetal heart in the normal fetus and those with congenital heart diseases [8][9][10][11].…”
Section: Real-time 3d Fetal Echocardiographymentioning
confidence: 99%
“…The frame rate of the system, the number of pictures per second (the frame rate being in the region of 20-28 frames per second), is fairly adequate in order to resolve the definition of the heart as it moves. There have been some reports on real-time 3D sonographic observation of the fetal heart in the normal fetus and those with congenital heart diseases [8][9][10][11].…”
Section: Real-time 3d Fetal Echocardiographymentioning
confidence: 99%
“…2,6 One of the major advantages of real-time 3D echocardiography is the fact that cardiac gating is not required. Because real-time 3D imaging yields volumetric data instantaneously, it also remains unaffected by random fetal motion.…”
Section: Discussionmentioning
confidence: 99%
“…1 There have been several reports on real-time 3-dimensional (3D) sonographic examination of the fetal heart. [2][3][4][5][6][7] One of the major advantages of real-time 3D echocardiography is that gating of the heart rate is not required. Using such a system, rendered 3D images of the beating fetal heart can be obtained instantaneously.…”
mentioning
confidence: 99%
“…Ninety volume datasets were randomly selected for blinded analysis for the identification of CHDs. The authors reported that the median (range) sensitivity, specificity, positive and negative predictive values as well as false positives and false negatives for the identification of fetuses with CHDs were: 93% (77-100), 96% (84-100), 96% (83-100), 93% (79-100), 4.8% (2.7-25), 6.8% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) respectively. Moreover, there was excellent inter-centre agreement (Kappa = 0.97) in the identification of CHDs.…”
Section: Accuracy and Reproducibility Of 4d Us In The Prenatal Diagnomentioning
confidence: 99%
“…Accumulating evidence indicates that 4D US facilitates examination of the fetal heart [1][2][3][4][5][6][7][8][9][10][11][12] . Thus, 4D fetal echocardiography has the potential to reduce the operator dependency of two-dimensional (2D) US.…”
Section: Introductionmentioning
confidence: 99%